Kamila BARANIECKA-OLSZEWSKA, World War II Historical Reenactment in Poland: The Practice of Authenticity, London 2021, Routledge, 368 s., ISBN 978-1-00-305445-0 - Šubrtová, Tereza (Dějiny – teorie – kritika, 2025)
Book review